Acellular Dermal Allograft for VestibuloplastyÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬ÂAn Alternative to Autogenous Soft Tissue Grafts in Preprosthetic Surgical Procedures: A Clinical Report - Monish Bhola, DDS, MSD,1 Donald H. Newell, DDS, MSD,2 and (Journal of Prosthodontics, 2003)
Various vestibular extension procedures have been described in the literature over the past 6 decades, including the use of free gingival grafts